PENGARUH PEMBERIAN EKSTRAK KULIT BUAH RAMBUTAN (Nephelium lappaceum) TERHADAP JUMLAH SPERMATOZOA TIKUS JANTAN GALUR WISTAR (Rattus novergicus) YANG DIINDUKSI PAKAN TINGGI LEMAK - Kerin Victoria Sipahutar (2019)
Obesity caused by high fat diet lead to an altered reproductive hormonal profile and production of oxidative stress. These conditions can be overcome by antioxidants. The antioxidants used in this study is rambutan fruit peel extract. This study was aimed to determine the effect of rambutan fruit peel extract towards total sperm count in Wistar rats inducted with high-fat feed. This research design was post test only control group, subjects were 30 male Wistar rats divided into 5 groups : Group 1 (Positive Control) was given high-fat feed, Group 2 (Treatment Control Group) was given 15mg/kgBW rambutan fruit peel extract, whereas group III,IV,V (Treatment Group) was given extract of rambutan skin with a dose of 15, 30, and 60 mg/kgBW, respectively. Treatment was given for 81 days. The result of this study shows that rambutan fruit peel extract with doses of 15, 30, and 60 mg/kgBW significantly increase total sperm count in Wistar rats inducted with high-fat feed. The outcome using Kruskal Wallis show result pvalue 0,010 (CI 95%). Antioxidant compounds found in rambutan fruit peel extract significantly increase total sperm count in Wistar rats inducted with highfat feed, with the greatest efficacy on the dose of 15mg/kgBW.